2017
DOI: 10.1186/s12862-017-1055-3
|View full text |Cite
|
Sign up to set email alerts
|

Landscape genomics reveal that ecological character determines adaptation: a case study in smoke tree (Cotinus coggygria Scop.)

Abstract: BackgroundThe adaptive evolution of species response to environment are the key issues in molecular ecology and evolutionary biology. The direction of adaptive differentiation of species in regions lacking strong selection pressure is usually diverse. However, the driving mechanism of the diverse adaptive differentiation for regional species is still undetermined to date. In this study, we used landscape genomics modelling to infer the adaptive evolution of Cotinus coggygria in China’s warm-temperate zone.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Here, the results of LFMM analysis showed that Sr6, Bio6, Bio4, and Wvp1 were associated with the highest numbers of EAL, which suggested that these environmental variables play a major role on the genetic differentiation of P. stenoptera genome. Recent landscape genomic studies have proposed a hypothesis that environmental variables related to ecological habitats of species play key roles in driving adaptive differentiation of species genome [ 2 , 14 , 15 ]. Among the four environmental variables associated with the largest number of adaptive loci, Sr6 was associated with the ecological habitat of “prefered light”, and Bio6 and Wvp1 were associated with the ecological habitat of “warm and humid environment”.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, the results of LFMM analysis showed that Sr6, Bio6, Bio4, and Wvp1 were associated with the highest numbers of EAL, which suggested that these environmental variables play a major role on the genetic differentiation of P. stenoptera genome. Recent landscape genomic studies have proposed a hypothesis that environmental variables related to ecological habitats of species play key roles in driving adaptive differentiation of species genome [ 2 , 14 , 15 ]. Among the four environmental variables associated with the largest number of adaptive loci, Sr6 was associated with the ecological habitat of “prefered light”, and Bio6 and Wvp1 were associated with the ecological habitat of “warm and humid environment”.…”
Section: Discussionmentioning
confidence: 99%
“…All individuals were genotyped using SCoT markers. Despite its inherent defects lacking DNA sequence information, the SCoT marker has been used for landscape genomic studies because it has the advantages of non-requirement for genomic information, high repeatability, and high throughput [ 2 , 14 , 15 ]. After preliminary screening of the polymorphism and reproducibility of all SCoT primers [ 25 ], nine primers (SCoT5, SCoT9, SCoT16, SCoT18, SCoT25, SCoT27, SCoT30, SCoT31, and SCoT35) were selected for polymerase chain reactions (PCRs).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This raises the fundamental question of which environmental factors play key roles in promoting adaptive divergence. Recent studies have suggested that environmental factors related to ecological niche dimensions are the main forces driving adaptive differentiation 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Different from landscape genetics, landscape genomics requires a sufficient number of molecular markers to cover the entire genome. Emphasis is placed on adaptive evolution at the genome level ( Miao et al, 2017 ). Landscape genetics, however, is biased toward using a relatively small number of molecular markers to reveal the relationship between environmental factors and the spatial genetic structure of populations ( Dionne et al, 2008 ; Poelchau and Hamrick, 2012 ; Manel and Holderegger, 2013 ).…”
Section: Introductionmentioning
confidence: 99%